Feminism and Firearms: Gun Ownership, Gun Carrying, and Women's Empowerment. (February 2022) - Kelley, Margaret S.
In this article, I use the 2018 Guns in American Life Survey (GALS) to investigate the relationship between feminist identity, gun ownership, gun carrying, and women's empowerment. Notably, while identifying as a feminist lessens the likelihood that a woman will own a gun, of women who own handguns, feminists are more likely to carry their guns all or most of the time. Past victimization is associated with ownership and carrying, confirming genuine concern by women about their safety. Finally, findings reveal that women are more empowered by guns than are men and the relationship is moderated by age. Results are discussed in light of the current American gun culture focused on self-defense and a carry mindset that some women develop as feminist culture in action.